Effect of thermal liquefaction on quality, chemical composition and antibiofilm activity against multiresistant human pathogens of crystallized eucalyptus honey. (15th December 2021) - Villacrés-Granda, Irina; Proaño, Adrian; Coello, Dayana; Debut, Alexis; Vizuete, Karla; Ballesteros, Isabel; Granda-Albuja, Genoveva; Rosero-Mayanquer, Hugo; Battino, Maurizio; Giampieri, Francesca; Alvarez-Suárez, José M.
Highlights: Thermal liquefaction (TL) did not affect the quality parameters of eucalyptus honey (EH) TL affected chemical composition, antioxidant capacity and antibacterial components of EH. TL did not affect the antibiofilm activity of HE in MRSA, but it did in P. aeruginosa. TL at 60 °C affected the antibiofilm activity of EH in both pathogens. Structural changes in biofilm architecture caused by EH was not affected by TL. Abstract: Thermal liquefaction is a conventional method used by beekeepers to liquefy crystallized honey. However, an abusive use of heat may affect its quality, chemical composition and bioactivity. The purpose of this study was to investigate the effect of thermal liquefaction on the quality, chemical composition and antibiofilm properties of eucalyptus honey. Thermal liquefaction (at 45 and 60 °C) did not affect the honey's quality; however, a significant reduction in the reducing capacity, total phenolic content and hydrogen peroxide content was observed. At 60 °C, a significant reduction in the honey's ability to inhibit biofilm formation was observed in Pseudomonas aeruginosa, as well as a reduction in its ability to remove preformed biofilms in both Staphylococcus aureus and Pseudomonas aeruginosa . Structural changes in biofilm architecture caused by honey were not affected by thermal treatment. Therefore, we recommend liquefaction at 45 °C as the most convenient for honey liquefaction without affecting its characteristics.